EVALUASI PROGRAM PENINGKATAN KUALIFIKASI S1 MELALUI DUAL MODE SYSTEM (DMS) KEMENTERIAN AGAMA REPUBLIK INDONESIA - Abdul Fattah (JTP - Jurnal Teknologi Pendidikan, 2016)
The focus of this study is to examine the effectiveness of S1-Qualification Improvement program for the teachers of Madrasah and PAI through Dual Mode System (DMS) at the Ministry of Religious Affairs, for the LPTK Rayon 10 IAIN Mataram. The specified targets are reviewed from five (5) components: context, input, process, product, and impact / output or outcomes. The model of research design used in this study is CIPP Stufflebeam evaluation model by adding outcomes (O) components. In general, it is concluded that the implementation of the S1-Qualification Improvement program through Dual Mode System (DMS) in LPTK Rayon 10 IAIN Mataram has been going well and in accordance with the guideline and rule standard set by the Ministry of Religious Affairs Republic Indonesia.